The Implementation of Group Investigation, Direct Learning and Motivation toward Learning Outcome of Pancasila and Citizenship Education (PPKn) - Rohmawati, Yeni; Wiryokusumo, Iskandar; Leksono, Ibut Priono (International Journal of Educational Technology and Learning, 2019)
Group Investigation (GI) is one of the complex methods in group learning that requires students to use high-order thinking skills. Direct Learning (DL) is one of the teaching approaches designed to support students’ learning processes related to declarative knowledge and well-structured procedural knowledge. DL can be taught by a gradual and step-by-step activity pattern. It is known that both models are related to student learning styles and learning outcomes. Learning outcome is a result of the learning process by using measurement tools, namely in the form of tests arranged in a planned manner, both written tests, oral tests, and deeds tests. This study was an experimental research. The population of the study were all class of 10th Grade from two religion-based senior high school, MA Al Khairiyah Balen and MA Muhammadiyah 1 Sumberrejo Bojonegoro, two classes from academic year of 2017/2018 in a total of 142 students. The researchers chose as sample for the experimental group was the class X of Natural Science (IPA) amounting to 36 students and the control class was the class X of Social Science (IPS) totaling 36 students. Sample selection is done by cluster sampling technique.